Pedagogical and Design Aspects of a Blended Learning Course - Precel, Karen; Eshet-Alkalai, Yoram; Alberton, Yael (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2009)
Based on recent research reports, the blended learning model, which combines face-to-face and online learning, is now the preferred model for online course design. Its superiority over online learning, which lacks face-to-face interaction, is evident from studies that examined both student achievement and satisfaction. Nevertheless, there is ambiguity in the literature and in the field regarding the proper implementation of blended learning and the optimal proportions between online and F2F components in various learning scenarios. The range of contradictory reports in recent literature on the potential of different blended learning models shows the need for more research on specific blended learning courses in order to establish proper standards for effective course design and implementation. The present evaluation study focuses on students’ perceptions of pedagogical and design issues related to a new model for blended learning that was used in a graduate-level course at the Open University of Israel. Fifty-eight of the course’s 91 students participated in the study and completed a questionnaire regarding three major aspects of the course design: (1) pedagogy, (2) textbook format (print vs. digital), and (3) learning environment usability. The results illustrate the importance of completing the pedagogical and visual design of online learning in advance. Also, the course model suggests ways to bridge the gaps between students and instructors and students and their peers, which are typical of online learning in general and open universities in particular.